MYER INDEX IN SIX POPULATION GROUPS OF(ACCORDING TO SIZE) - Z.Pour Ansari; V.Nahapetian (Tehran University of Medical Sciences, 1980)
In this study Myer Index was calculated for six groups of a sample of urban and rural population of Iran, classified by population size. The data used were information collected on 146116 urban and 158124 rural populations, for estimation of death, birth and growth rates in Iran. The results indicate: The range of the index varies between 23.14-68.06 for women and 28.41-69.62 for men (urban or rural). No considerable difference was observed between the indices of some towns of group 5 (with small population) and the rural population (group six). There was a positive and significant correlation between the Myer Index of men and the level of illiteracy. More study on other demographic, economic and health indices are suggested as a means of classification of urban and rural population other than population size.